1972
DOI: 10.1254/jjp.22.715
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON THE PHYSICAL DEPENDENCE OF A NEW CENTRAL ANALGESIC; 1-(m-METHOXYPHENYL)-2-DIMETHYLAMINOMETHYL CYCLOHEXANOL (1) HCL (CG-315)

Abstract: Since earlier studies with nalorphine in humans demonstrated analgesia (1, 2) without producing dependence of the morphine type (1-3), a considerable effort has been made to discover a drug having similar characteristics, but without undesirable psychic effects.Pentazocine was found to be in this category (4-7).
Recently, 1-(m-methoxyphenyl)-2-dimethylaminomethyl cyclohexanol (1) HCl (hereafter referred to as CG-315) was synthesized as a new central analgesic, by Grünenthal Co., Ltd., West Germany. He…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1973
1973
1973
1973

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, CG-315, a newly synthesized analgesic, shows neither the mitochondrial transformation nor fall in body wt. after withdrawal of the drug during chronic administration (2,3).…”
mentioning
confidence: 99%
“…On the other hand, CG-315, a newly synthesized analgesic, shows neither the mitochondrial transformation nor fall in body wt. after withdrawal of the drug during chronic administration (2,3).…”
mentioning
confidence: 99%
“…Furthermore, it has been demonstrated that CG-315, a new analgesic, did not produce physical dependence in our experiments (4) and showed no transformation of mitochondria after withdrawal (5), while codeine did cause a moderate transformation (6).…”
mentioning
confidence: 61%
“…The time course of the appearance of transformation coincides with that of profound loss in body wt. after withdrawal, the latter being the best index of physical dependence on morphine and related compounds (2)(3)(4).…”
mentioning
confidence: 99%